2011
DOI: 10.1007/s00702-011-0658-x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenines and intestinal neurotransmission: the role of N-methyl-d-aspartate receptors

Abstract: Gastrointestinal neuroprotection involves the net effect of many mechanisms which protect the enteral nervous system and its cells from death, dysfunction or degeneration. Neuroprotection is also a therapeutic strategy, aimed at slowing or halting the progression of primary neuronal loss following acute or chronic diseases. The neuroprotective properties of a compound clearly have implications for an understanding of the mechanism of dysfunctions and for therapeutic approaches in a number of gastrointestinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 93 publications
0
51
0
Order By: Relevance
“…Related to their role(s) in physiology, peripheral and central KP metabolites have recently received considerable attention as potential agents in human diseases ranging from cancer (61) to intestinal syndromes (62) and disorders of the endocrine (63), immune (64,65), and central nervous systems (20, 66 -69). Causal connections have been postulated either because genetic or biochemical KP abnormalities were found in specimens obtained from patients, as in schizophrenia (70 -76), or because studies in animals had predicted etiologically significant links.…”
Section: Discussionmentioning
confidence: 99%
“…Related to their role(s) in physiology, peripheral and central KP metabolites have recently received considerable attention as potential agents in human diseases ranging from cancer (61) to intestinal syndromes (62) and disorders of the endocrine (63), immune (64,65), and central nervous systems (20, 66 -69). Causal connections have been postulated either because genetic or biochemical KP abnormalities were found in specimens obtained from patients, as in schizophrenia (70 -76), or because studies in animals had predicted etiologically significant links.…”
Section: Discussionmentioning
confidence: 99%
“…Less is understood regarding the functions of kynurenic acid and quinolinic acid in the GI tract; however, both appear to be involved in immunoregulation (Keszthelyi et al, 2009). Interestingly, kynurenic acid may have anti-inflammatory properties in the GI tract (Kaszaki et al, 2012), and has been shown, in-vitro, to inhibit the proliferation of colon cancer cells (Walczak et al, 2014). **************************Insert Figure 2 Here****************************** 6.…”
Section: Tryptophan Metabolism Serotonin and The Kynurenine Pathwaymentioning
confidence: 99%
“…N-methyl-D-aspartate (NMDA) receptor consists of three subunits (NR1, NR2, and NR3) and is activated by Glu and glycine. Glycine is essential for NMDA receptor function with the glycine binding site being located on the NR1 subunit [129,130]. In higher (micromolar/millimolar) doses, KYNA acts on the strychnine-insensitive glycine binding site of the NMDA receptor [130].…”
Section: Kynurenic Acidmentioning
confidence: 99%